Location, location, location: a discrete choice experiment to inform COVID-19 vaccination programme delivery in the UK - Robert McPhedran; Natalie Gold; Charlotte Bemand; Dale Weston; Rachel Rosen; Robert Scott; Tim Chadborn; Richard Amlôt; Max Mawby; Ben Toombs (BMC, 2022)
Abstract Background Large-scale vaccination is fundamental to combatting COVID-19. In March 2021, the UK's vaccination programme had delivered vaccines to large proportions of older and more vulnerable population groups; however, there was concern that uptake would be lower among young people. This research was designed to elicit the preferences of 18-29-year-olds regarding key delivery characteristics and assess the influence of these on intentions to get vaccinated, to inform planning for this cohort. Methods From 25 March to 2 April 2021, an online sample of 2012 UK adults aged 18-29 years participated in a Discrete Choice Experiment. Participants made six choices, each involving two SMS invitations to book a vaccination appointment and an opt-out. Invitations had four attributes (1 × 5 levels, 3 × 3 levels): delivery mode, appointment timing, proximity, and sender. These were systematically varied according to a d-optimal design. Responses were analysed using a mixed logit model. Results The main effects logit model revealed a large alternative-specific constant (β = 1.385, SE = 0.067, p < 0.001), indicating a strong preference for 'opting in' to appointment invitations. Pharmacies were dispreferred to the local vaccination centre (β = − 0.256, SE = 0.072, p < 0.001), appointments in locations that were 30-45 min travel time from one's premises were dispreferred to locations that were less than 15 min away (β = − 0.408, SE = 0.054, p < 0.001), and, compared to invitations from the NHS, SMSs forwarded by 'a friend' were dispreferred (β = − 0.615, SE = 0.056, p < 0.001) but invitations from the General Practitioner were preferred (β = 0.105, SE = 0.048, p = 0.028). Conclusions The results indicated that the existing configuration of the UK's vaccination programme was well-placed to deliver vaccines to 18-29-year-olds; however, some adjustments might enhance acceptance. Local pharmacies were not preferred; long travel times were a disincentive but close proximity (0-15 min from one's premises) was not necessary; and either the 'NHS' or 'Your GP' would serve as adequate invitation sources. This research informed COVID-19 policy in the UK, and contributes to a wider body of Discrete Choice Experiment evidence on citizens' preferences, requirements and predicted behaviours regarding COVID-19.